Comparison of emissions from steam- and water-assisted lab-scale flames. (15th October 2021) - Bello, Olanrewaju W.; Zamani, Milad; Abbasi-Atibeh, Ehsan; Kostiuk, Larry W.; Olfert, Jason S.
Highlights: "Assisted" flares are commonly used in the oil and gas industry to reduce black carbon emissions. An emission comparison study of water- and steam-assist on turbulent non-premixed flames was carried out. Liquid water reduced black carbon and NO x emissions more than steam for an equivalent mass of assist fluid. The enhanced reduction in emissions when using liquid water was most likely due to thermal effects. Abstract: Steam-assisted flares are often used in the downstream oil and gas industries as a strategy to produce "smokeless" combustion. The addition of liquid water to flames is also known to suppress soot formation but is rarely done in industrial flares. Since utilizing liquid water saves the energy required to convert water to steam, it was useful to investigate the extent to which liquid water and steam individually affect soot formation and NO x emissions during flaring. The three fuels used in this study were pure propane, pure methane, and a mixture of 90% methane and 10% propane, the latter approximating the typical volumetric higher heating value of Alberta flare gas. The fuel flow rates were fixed at 20 standard L/min in all cases, and liquid water and steam were introduced into the fuel's combustion zone, while their flow rates varied from 0 to 30 g/min. The results show that both liquid water and steam reduce NO x and soot mass emissions; however, liquid water reduces NO x and soot emissions more than steam. Likewise, the total particle number concentration and the particle sizes decrease with an increase in liquid water and steam. Simultaneously, liquid water reduces the total particle number concentration more than steam at the same assist flow rate, but a slight difference in their particle sizes. The thermodynamic mechanism appears to play the major role in controlling emissions. These results suggest that water-assisted flares in the oil and gas industries would likely produce lower emissions with a lower operating cost than steam-assisted flares.